2012
DOI: 10.1051/0004-6361/201218879
|View full text |Cite
|
Sign up to set email alerts
|

Circum-planetary discs as bottlenecks for gas accretion onto giant planets

Abstract: Context. With hundreds of exoplanets detected, it is necessary to revisit giant planets accretion models to explain their mass distribution. In particular, formation of sub-jovian planets remains unclear, given the short timescale for the runaway accretion of massive atmospheres. However, gas needs to pass through a circum-planetary disc. If the latter has a low viscosity (as expected if planets form in "dead zones"), it might act as a bottleneck for gas accretion. Aims. We investigate what the minimum accreti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 25 publications
(54 reference statements)
0
34
0
Order By: Relevance
“…This torque was already considered in Rivier et al (2012) in their 2D simulations. The authors there assumed that in the inviscid case the torque is deposited only in the very inner part of the CPD.…”
Section: Planetary Accretionmentioning
confidence: 88%
See 2 more Smart Citations
“…This torque was already considered in Rivier et al (2012) in their 2D simulations. The authors there assumed that in the inviscid case the torque is deposited only in the very inner part of the CPD.…”
Section: Planetary Accretionmentioning
confidence: 88%
“…However, we cannot provide a reliable estimate of the mass of the CPD with our isothermal simulations, particularly in the limit of vanishing viscosity, which could lead to a significant pileup of material in the CPD. An order of magnitude analytic estimate in Rivier et al (2012) reported a CPD mass of ∼10 −3 M J . Even assuming a CPD mass of 0.01 M J , the stellar torque would lead to an accretion rate of only 2.5 × 10 −6 M J yr −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tidal force can drive global spiral arms and shocks in circumplanetary disks, leading to accretion. 2D and 3D simulations (Rivier et al 2012;Szulágyi et al 2014) have shown that the accretion induced by tidal forces is 2 × 10 −10 M yr −1 assuming that dissipation in the circumplanetary disk leads to a steady accretion. However, shock dissipation is unlikely to be uniform throughout the circumplanetary disk and mass may pile up in the disk by shock dissipation.…”
Section: Caveatsmentioning
confidence: 99%
“…Another possibility is that accretion is regulated by the circumplanetary disc that forms around high-mass planets (Ayliffe and Bate 2009a,b;Ward and Canup 2010). These subdiscs are discussed in detail elsewhere in this volume; here we just mention that recent simulations show that the circumplanetary disc may indeed be a bottleneck (Rivier et al 2012;Szulágyi et al 2014). …”
Section: Accretion Inside Gapsmentioning
confidence: 99%